Effect of food additives on human health (Eurasian Journal of Ecology, 2016)
The definition of food additives are given in the article, examines the causes the wide use of food additives by food manufacturers . The classification of food additives based on their technological functions are provided. It wasestablished that allowed for application food additives are not dangerous to human health, but some of them can cause of allergic reactions or other side effects that are not immediately appear . The table of food additives with any harmful for human health are provided in the article. Using of food additives is possible only after their safety check . Adding food additives should not increase the risk , the possible adverse effects of the product on the consumer's health , as well as reduce its nutritional value. The effect of any chemical substance, including food additives , on the human bodydepends on the individual features of the body and on the amount of substance.
Keywords: human health; food additives; food colorings; preserving agents; antioxidants; stabilizers; emulsifiers; unclassified additives; biocatalysts